Yeast as a Biological Platform for Vitamin D Production: A Promising Alternative to Help Reduce Vitamin D Deficiency in Humans - Martinez-Fernandez, C; Palacios-Pino, J; Kessi-Perez, E; Gonzalez-Chia, A (John Wiley and Sons Ltd, 2022)
Vitamin D is an important human hormone, known primarily to be involved in the intestinal absorption of calcium and phosphate, but it is also involved in various nonskeletal processes (molecular, cellular, immune, and neuronal). One of the main health problems nowadays is the vitamin D deficiency of the human population due to lack of sun exposure, with estimates of one billion people worldwide with vitamin D deficiency, and the consequent need for clinical intervention (i.e., prescription of pharmacological vitamin D supplements). An alternative to reduce vitamin D deficiency is to produce good dietary sources of it, a scenario in which the yeast Saccharomyces cerevisiae seems to be a promising alternative. This review focuses on the potential use of yeast as a biological platform to produce vitamin D, summarizing both the biological aspects of vitamin D (synthesis, ecology and evolution, metabolism, and bioequivalence) and the work done to produce it in yeast (both for vitamin D2 and for vitamin D3), highlighting existing challenges and potential solutions. © 2022 John Wiley & Sons Ltd.